PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN BAGIAN LAPANGAN (Studi Pada PT. Siak Pertambangan dan Energi kabupaten Siak) - Eriyanto "; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Siak Mining and Energy (SPE) Ltd. Co of Siak regency is one of regional ownedenterprises (BUMD) owned by Siak regency, Riau where this company is a work over andwell services. From the first established, Siak Mining and Energy Ltd. Co of Siak regencyhas conducted training and education for its employees through Cepu Oil and Gas TrainingCenter. Implementation of training and education is expected to maximize the productivityor employees performance of Siak Mining and Energy (SPE) Ltd. Co of Siak regency. Theaim of this study is to analyze training and education applied to employees of outside area,to analyze performance of outside area and analyze influence of training and educationtoward employees performance of Siak Mining and Energy (SPE) Ltd. Co of Siak regency.The sample is 50 respondents where use purposive sampling technique. Data are collectedby spreading questionnaire to respondent and the data are analyzed using Uij-t and SimpleLinear Regression. Statistical analysis using SPSS version 17 is used to analyze data. Thefindings of study indicated where coefficient of determination is 0.823. It shows thattraining and education affect employees performance is 82.3%.Keyword: Education and Training Performance, Employees Of Outside Area